Pengaruh Penyuluhan Metode Demonstrasi terhadap Pengetahuan Infeksi Nosokomial pada Pasien Rawat Inap - I Komang Budiana; I Made Rio Dwijayanto; I Ketut Sudiyono (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Nosocomial infections, known as Healthcare Associated Infections (HAIs), occur throughout the world. The patient's family has an important role in the prevention of Nosocomial Infection by improving handwashing behavior well, but the implementation of handwashing in the patient's family has not run optimally because many patient families do not know how to wash their hands properly. This study used a pre-experimental design with the design of one group pretest-posttest test design, the sample performance in this study was carried out by a Non-probability sampling technique with a purposive sampling analysis of this study using the Wilcoxon Signed Rank Test. The subjects in this study were families of hospitalized patients in the Flamboyan Room Negara Hospital which numbered 92 people. The measuring instrument used in this study used a knowledge questionnaire on nosocomial infections. There were influences before and after the extension of the demonstration method with the family characteristics of inpatients, most of the education level was junior high school, with the most adult age range 26-45 with a male gender. There is an influence on the extension of the demonstration method on the knowledge of nosocomial infections and this counseling can increase the knowledge of families of inpatients in the Flamboyan Room Negara Hospital in 2019.